Nb-Doped TiO2 Photocatalysts Used to Reduction of CO2 to Methanol - Nogueira, M. V. [UNESP]; Lustosa, G. M.M.M. [UNESP]; Kobayakawa, Y.; Kogler, W.; Ruiz, M. [UNESP]; Monteiro Filho, E. S. [UNESP]; Zaghete, M. A. [UNESP]; Perazolli, L. A. [UNESP] (Wiley, 2018)
In pursuit of higher photoactivity, Nb-doped TiO2 powders were evaluated in the reduction of CO2. The replacement of Ti by Nb in the crystalline structure of TiO2 promoted methanol formation. Nb-doped TiO2 powders were successfully synthesized in Nb concentrations of 0.0, 0.5, 1.0, and 2.5% (w/w = weight/weight) using the Pechini method. The materials were calcined at 500°C for two hours to promote the formation of the anatase crystalline phase. After characterization, the powders were modified through an Nb0 magnetron sputtering deposition using a metallic target in vacuum conditions of 2 × 10-3 torr, with a deposition time of 10 minutes, and calcination again at 500°C for two hours. The resulting powders showed a surface area up to 30 m2/g. The Pechini method promoted the substitution of Ti4+ for Nb4+ as observed using XRD and XPS techniques at the crystalline structure and at the surface of the powder. Furthermore, the presence of Nb0 was also observed at the powder's surface. The presence of Nb in the crystalline structure increased the photoactivity of powders when compared to nonmodified TiO2 powders, while the Nb0 deposition at the powder's surface decreased the photoactivity for all the investigated compositions.